Formulasi bubur bayi MPASI yang diperkaya hidrolisat protein ikan lele dumbo (Clarias gariepinus) - Veriani Aprilia; Febrina Suci Hati (Alma Ata University Press, 2016)
ABSTRACTBackground: Malnutrition become the problem in Indonesia. Complementary feeding has the role in solving it. Most of commercial complementary feeding are enriched by vegetable protein, whereas animal protein has more complete amino acid and better digestibility. Unfortunately, consuming animal proteinoften raises concern because of its allergenicity. Catfish (Clarias gariepinus) can be used as a source of high animal protein in the diet that may solve the nutritional problem after reduction of its allergen.Objectives: To develope formulate of complementary feeding porridge enriched with hydrolized protein from catfish muscle.Methods: This was experimental study. HPIL and HPIK was enzymatic hydrolized products of catfish using crude and commercial papain, respectively. Overall and partial hedonic test used 23 mothers as panelists, then selected formula were tested its acceptance by 9 babies using face scale. Nutrient content of porridge were analyzed for protein, carbohydrate, fat, protein, and water.Results: Hydrolysis of catfish using papain made the changes in color, taste, and aroma. The bitter taste limited the uses, maximum amount was 25%. Porridge with the addition of HPIK were chosen by mothers and babies panelists, whereas HPIL did not. Protein content of formulated product were lower than commercial product, but carbohydrate and fat content were higher.Conclusions: Porridge formula with addition of 25% HPIK my be developed as alternative product of complementary feeding.KEYWORDS: protein, papain, catfish, protein hydrolisate, complementary feedingABSTRAKLatar belakang: Kekurangan gizi masih menjadi masalah di Indonesia. MPASI memiliki peran penting dalam mengatasi masalah tersebut. MPASI pada umumnya diperkaya oleh protein nabati, padahal protein hewani mengandung asam amino dan daya cerna yang lebih baik. Namun demikian, protein hewanimeningkatkan risiko alergi pada bayi. Lele (Clarias gariepinus) dapat dijadikan alternatif sumber protein hewani karena ketersediaan yang banyak dan harganya yang murah. Diperlukan suatu teknologi untuk mengurangi tingkat alerginya dan formulasi yang tepat dibutuhkan agar dapat diterima oleh bayi.Tujuan: Formulasi bubur bayi MPASI yang diperkaya hidrolisat protein ikan lele dumbo.Metode: Jenis penelitian ini adalah eksperimental. HPIL dan HPIK merupakan hidrolisat protein ikan lele dumbo yang masing-masing dihidrolisis secara enzimatis menggunakan enzim papain kasar dan papain komersial. Uji kesukaan keseluruhan dan parsial menggunakan 23 panelis ibu, kemudian formula terpilihdiujikan daya terimanya oleh 9 bayi menggunakan skala raut muka. Uji nilai gizi bubur bayi meliputi kadar protein, karbohidrat, lemak, protein, dan air.Hasil: Proses hidrolisis kimiawi protein ikan lele dumbo menggunakan enzim papain menyebabkan perubahan warna, rasa, dan aroma produk. Adanya perubahan sifat tersebut menyebabkan penambahannya ke dalam formulasi bubur MPASI hanya sampai kadar 25%. Di atas kadar tersebut, produk berasa pahit. Hasil uji sensoris produk formulasi HPIK dapat diterima oleh panelis ibu dan bayi, sedangkan produk HPIL tidak. Kandungan protein produk formulasi lebih rendah dibanding bubur komersial, namun kandungan karbohidrat dan lemak lebih tinggi.Kesimpulan: Formula bubur bayi dengan penambahan 25% HPIK dapat dikembangkan menjadi alternatif produk MPASI.KATA KUNCI: protein, papain, lele dumbo, hidrolisat protein, MPASI